Analysis of Differentiation Strategy, Cost Leadership and Market Orientation on Product Excellence - Kusnanto, Eri; Azhari, Cindy (AGUSPATI Research Institute, 2024)
This study aims to determine the effect of differentiation strategy, cost leadership, and market orientation on product excellence. The research approach taken is to use a qualitative approach. The population of this study were all employees, especially in the field of sales and marketing. From the existing population, the sample was set at 60 people. The instrument used in this research is a questionnaire. The analytical tool used to qualitatively determine the effect between variables in this study used multiple linear regression analysis. The results of this study indicate that Differentiation Strategy has a positive effect on product excellence, Cost leadership has a positive effect on product excellence. Market orientation has no effect on product excellence. And simultaneously all independent variables have a positive effect on product excellence. This is evidenced by the coefficient of determination which is positive and the significant value is less than 0.05 or where the F-count value is greater than the F-table value. Managerial implications include the importance of companies to consider implementing differentiation and cost leadership strategies to increase their product advantage in a competitive market. Future research implications include the need for further research to understand other factors that may affect product excellence in this industry context.